METACOGNITIVE STRATEGIES IN MEDIATING EFL ADULT LEARNERS’ SELF-REGULATED LANGUAGE LEARNING: A SYSTEMATIC REVIEW - Siregar, Renol Aprico; Lengkanawati, Nenden Sri; Damayanti, Ika Lestari (LLT Journal: A Journal on Language and Language Teaching, 2024)
Although many studies focus on enhancing resource assistance and the advancement of adult learners' knowledge and abilities, there is a paucity of studies on the theoretical views that define strategies for assisting adults in learning independently. To fill this gap, this study draws on previous research to elaborate on why metacognitive strategies are suitable for adults’ self-regulated learning (SRL), and how metacognitive strategies promote SRL. As this study employed a systematic review, a rigorous search scheme was implemented across multiple databases, resulting in the selection of relevant studies based on predetermined inclusion and exclusion criteria. The selected articles were assessed for quality, and data extraction was performed to identify key characteristics of the studies. The synthesis of the existing literature underscores the suitability of metacognitive strategies in EFL adult learners' self-regulated learning. The findings reveal that incorporating metacognitive strategies helps cultivate SRL in EFL adult learners, owing to their cognitive maturity, pre-existing knowledge, and life experiences. In addition, the metacognitive strategy helps EFL adult learners enhance their awareness of cognitive processes, regulate learning behaviours, and optimize language learning outcomes. Regarding the role, metacognitive strategy is one of the key components of SRL. Some practical recommendations are made to support teachers in facilitating adults’ self-regulated language learning.